Zachování fertility u žen s karcinomem prsu před gonadotoxickou léčbou - Halászová, N; Crha, I; Huser, M; Weinberger, V; Žáková, J; Ješeta, M; Lousová, E; Filipinská, E; Ventruba, P (Ceska gynekologie, 2017)
OBJECTIVE: To present current options and own experiences with ovarian stimulation in young women with breast cancer before gonadotoxic therapy. DESIGN: Review article with own experiencies. METHODS: Literary search, analysis of own experiences with complex therapy in women with breast cancer planning pregnancy, definitions of stimulating protocols, using methods of assisted reproduction. SETTING: Department of Obstetrics and Gynecology, Faculty of Medicine, Masaryk University and University Hospital Brno. RESULTS: Embryo and oocyte cryopreservation are important methods of fertility preservation requiring controlled ovarian stimulation before the start of chemotherapy. Current studies demonstrante effectivenes of this special stimulating protocol and did not find negative side effects such a progression of the breast cancer. Since January 2016 to June 2016 we performed controlled ovarian stimulation and oocyte retrieval in three patients with breast cancer before chemotherapy. We used short stimulation protocol with recombinant FSH, GnRH agonists and letrozole and retrieved 13, 12 and 9 oocytes. We cryopreserved 8 and 6 embryos, one woman prefered freezing of 12 oocytes. During the stimulation estradiol level did not exceed 1,6 nmol/l. CONCLUSION: Neither the normal nor the cancerous cells in the breast react to the gonadotropins FSH, LH, nor to hCG. Conversely, there is a cellular proliferation and an increase in cancer cell lines with oestrogen receptors with exposure to oestrogen, and it is dose - dependent. The special stimulation protocol with FSH, GnRH agonists and letrozole is effective in gain of efficient amount of gamets with minimal increase of estradiole level. Current study reviews did not find higher risk of progression of breast cancer in association with ovarian stimulation. It is important to respect the recomendation of oncology committee and to effectively suppress the estradiol level.
Keywords: Cryopreservation; nádory prsu; Ovulation Induction; Female; cryopreservation; fertilizace in vitro; letrozole; breast cancer; ženské pohlaví; Oocytes; Oocyte Retrieval; lidé; Antineoplastic Agents; protinádorové látky; těhotenství; oocyty; Breast Neoplasms; kryoprezervace; odběr oocytu; chemotherapy; oncofertility ovarian stimulation.; Pregnancy; zachování plodnosti; Fertilization in Vitro; indukce ovulace; Fertility Preservation; Humans